PENGARUH PAJAK DAERAH TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN GORONTALO PERIODE 2015-2019 - Ramlah Alkatiri; Nur Eng Mokodompit; Mochtar N. Kilo (Universitas Muhammadiyah Gorontalo, 2021)
The objective of research were: 1) to determine that the Local Taxes ia influenced on Economic Growth at Gorontalo Regency in 2015-2019 and 2) to determine, how much the influence value between local taxes and the economic growth of Gorontalo Regency for the period 2015-2019. The method used quantitative research approach with the type of research was an explanatory research. The result of research obtained that 1). There ia the influence of Local Taxes on Economic Growth at Gorontalo Regency in periode of 2015-2019, this is proven through statisical test which is obtained significance value 0.006 small than α 0.05, and 2) The coefficient of determination obtained is 0.921, this explains that the level of influence of the local tax variable on economic growth is very strong and has a positive value. Keywords: Local Taxes, Economic Growth